2007
DOI: 10.1177/1538574407301430
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Results of Endovascular Infrarenal Abdominal Aortic Aneurysm Repair in High-Risk Patients

Abstract: Short-term and midterm clinical outcomes after endovascular repair of abdominal aortic aneurysms (AAAs) have been well documented. Evaluation of longer term outcomes is now possible. Here we describe our initial 100 high-risk patients treated with endovascular aneurysm repair (EVAR), all with a minimum of 5 years of follow-up. A retrospective review of prospectively recorded data in a departmental database was undertaken for the first 100 consecutive EVAR patients with a minimum of 5 years (range, 60-105 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, our 30-day and 1-year mortality rates were lower for EVAR and higher for OSR. As noted by Nagpal et al, 17 however, the absence of a standardized reporting between studies of high-risk patients makes comparisons difficult. Almost twothird of patients in our study were at SVS/ISCVS grade II and ASA grade 4.…”
Section: Discussionmentioning
confidence: 95%
“…However, our 30-day and 1-year mortality rates were lower for EVAR and higher for OSR. As noted by Nagpal et al, 17 however, the absence of a standardized reporting between studies of high-risk patients makes comparisons difficult. Almost twothird of patients in our study were at SVS/ISCVS grade II and ASA grade 4.…”
Section: Discussionmentioning
confidence: 95%
“…Smaller retrospective registry studies in high-surgicalrisk patients undergoing EVAR have shown operative mortality rates of 4.3% to 5% and a 3-year survival of 70% to 85%. 8,9 A recent analysis of patients from the United Kingdom (UK) EVAR trials, using a modified version of the Customized Probability Index to allocate fitness scores for all patients, found EVAR convincingly to favor only the good-fitness group in terms of 30-day mortality. 10 For midterm survival, no benefit was found for either EVAR or OR across all fitness scores.…”
Section: Discussionmentioning
confidence: 98%
“…5 We continue to prefer EVAR in higher-risk individuals with suitable anatomy where there is no doubt that this less invasive technique offers a survival advantage, at least in the short term. 10 Endovascular repair in lower-risk patients, or those with a longer life expectancy, is reserved for those patients with more optimal anatomy that permits one to expect a more durable repair.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 Our patients represented a more disparate group with many more high-risk individuals who would have not have met the inclusion criteria of these randomized trials. 10 In addition to more advanced age, male gender was determined to be a significant predictor of EVAR use. This male predilection for EVAR has been observed previously and attributed to the suboptimal anatomy that women more frequently exhibit that precludes successful endovascular repair.…”
Section: Discussionmentioning
confidence: 99%